Global agenda for livestock research: Proceedings of a conference on development of livestock research priorities in Asia - Devendra, C.; Smalley, M.E.; Li Pun, H.H. (International Livestock Research Institute, 1998)
This proceedings presents the results and conclusions of ILRI's role in livestock research and development in Asia. It provides a detailed testimony of the success of the consultation, and especially about ILRI's commitment to form integrated programmes for livestock and agricultural research with national partners and others. Topics of discussion include ILRI's mission, vision, programme and collaboration; animal genetic resources in Asia, ILRI's Animal Health Improvement Programme, Sustainable Production Systems Programme; ruminant feed resources research, and partnerships with NARS for technology transfer.